In situ Combined Electrochemical Techniques for Conducting Polymers - Visy, Csaba; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book outlines methods to improve functioning of these polymer based devices - in particular, the multi-faceted cognition of these materials. In situ electrochemical techniques are studied to elucidate redox switching between non-conducting and conducting states. The book examines the advantages of combinations of in situ electrochemical techniques in a hyphenated mode for analyzing conducting polymers.
Brief introduction to the field of conducting polymers and allied areas -- Redox transformation of CPs, and the coupled phenomena (changes in: mass, volume, conductance, color, morphology etc.) -- Overview of in situ electrochemical methods to follow the redox transformations -- Combined in situ methods.
Keywords: Electrochemistry; Polymers; Analytical chemistry; Energy harvesting; Electrochemistry; Polymers; Analytical Chemistry; Energy Harvesting